64 Is an end of life care survey at the bereavement appointment acceptable to carers?. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - McLoughlin, Hannah; Stewart, Kay; Davies, James; Hanson, Andrea
Abstract : Aim: To explore the feasibility and acceptability of bereavement survey. Methods: We surveyed deceased patients' next of kin (NOK) on the care they felt their relative received in their last admission to hospital. The survey was conducted from July 2016 to June 2017 within a large teaching hospital. A 28 question survey focused on communication with the patient and those important to them, management of their symptoms, care and dignity shown to the patient, fluids and nutrition at end of life, and care of those persons important to the patient. This mirrored the local and national end of life care guidance. The survey was initially posted to the deceased patients registered NOK 2–6 weeks after death. However it became apparent that the details for the NOK were not fully completed in the hospital records and this only allowed contact with 39% of NOK. From September 2016 it was decided to trial distributing the survey at the bereavement appointment, this is the time when the NOK receives the death certificate. The survey was paired with a covering letter detailing bereavement support information and self-addressed envelope for return. Maternal and neonatal deaths, suicide, cases accepted by the coroner and deaths in A and E were excluded. The team also used their discretion when handing out surveys and if they felt it would complicate a person's grief they excluded them. Results: 297 completed surveys were returned over the 12 month period. There was only one complaint regarding the survey itself. This complaint related to a survey sent at 6 weeks. There were no verbal complaints to any staff members involved in the survey process and the process was acceptable to staff. Conclusion: This study suggests that it is acceptable to carers and staff to sensitively distribute a bereavement survey at the bereavement appointment.